On a Singular Second-Order Multipoint Boundary Value Problem at Resonance - S. A. Iyase; O. F. Imaga (International Journal of Differential Equations)
The aim of this paper is to derive existence results for a second-order singular multipoint boundary value problem at resonance using coincidence degree arguments.